1998
DOI: 10.1597/1545-1569(1998)035<0154:dpopap>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Primary and Permanent Dentition in Children with Unilateral Complete Cleft Lip and Palate

Abstract: Four distribution patterns in the cleft area were identified in both sets of dentition. Our findings of distribution patterns in UCLP patients support the hypothesis that there may be two odontogenic origins for maxillary lateral incisors. Clinicians involved in managing the dentition of UCLP patients should consider the high frequency of numerical variation both in and outside the cleft area before starting dental treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
26

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 0 publications
4
50
1
26
Order By: Relevance
“…sor can be present on either side of the cleft or on both sides suggesting that the maxillary process placode has the potential to give rise to an incisor (Tsai et al, 1998;Lourenco Ribeiro et al, 2003). Our data suggest that in rats the maxillary process dental placode on its own seems to be vestigial without the full capacity of inducing teeth whereas in humans it is able to induce the formation of incisors.…”
Section: Primary Dental Placode In the Maxillary Process Explains Thementioning
confidence: 71%
See 1 more Smart Citation
“…sor can be present on either side of the cleft or on both sides suggesting that the maxillary process placode has the potential to give rise to an incisor (Tsai et al, 1998;Lourenco Ribeiro et al, 2003). Our data suggest that in rats the maxillary process dental placode on its own seems to be vestigial without the full capacity of inducing teeth whereas in humans it is able to induce the formation of incisors.…”
Section: Primary Dental Placode In the Maxillary Process Explains Thementioning
confidence: 71%
“…Failure of the medial nasal and maxillary processes to fuse results in cleft lip in humans, which often affects the formation of the upper lateral incisor that develops in this region. In cleft lip patients, there are four tooth distribution patterns observed in the clefting area, between the central incisor and canine: one tooth is present medial to the cleft; one tooth is present lateral to the cleft; two teeth are present on either side of the cleft; or there is no tooth formed (Tsai et al, 1998;Lourenco Ribeiro et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Studies of subjects with clefts, by contrast, have found the prevalence of missing teeth to range from 18% to 30%, and missing teeth was found to occur approximately three times as frequently on the cleft side as on the noncleft side. [28][29][30][31][32][33] In the present study, 16 of the 36 subjects (44.5%) had missing permanent lateral incisors in the cleft region and 5 of the 36 subjects (13.9%) had missing teeth outside the cleft region. The prevalence (44.5%) of missing teeth in CL/P in this study was higher than that in past studies, ranging from 18% to 30%.…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence (44.5%) of missing teeth in CL/P in this study was higher than that in past studies, ranging from 18% to 30%. [28][29][30][31][32][33] With this in mind, these two phenotypes, clefting and missing teeth inside the cleft region, might be related in their genetic etiology. Therefore, in the present study, we tried to discover the genetic relations between clefting and missing teeth in the cleft region.…”
Section: Discussionmentioning
confidence: 99%
“…e cleft area has been shown to be susceptible to disturbances in the dentition. 7 Common ndings with previous studies include tooth agenesis within or peripheral to the cleft region, supernumerary teeth, impacted teeth, delayed dental development, and altered crown to root ratios. [8][9][10][11] e timing of the grafting procedures dependent upon allowing tooth eruption through the graft site and is most frequently performed between the ages of nine and eleven years.…”
Section: Methodsmentioning
confidence: 92%